Ryanodine receptors and cardiac function - Eisner, David (Henry Stewart Talks, 2007)
Introduction to Calcium cycling in the heart, How to measure SR and sarcolemmal Calcium fluxes, What controls SR Calcium content, The effects of changing the open probability of the RyR, The link between Calcium and arrhythmias, Mechanisms responsible for alternans in the heart